Diverse Microorganisms in Sediment and Groundwater Are Implicated in Extracellular Redox Processes Based on Genomic Analysis of Bioanode Communities - Arbour, Tyler J.; Gilbert, Benjamin; Banfield, Jillian F. (Frontiers in Microbiology, 2020)
Extracellular electron transfer (EET) between microbes and iron minerals, and syntrophically between species, is a widespread process affecting biogeochemical cycles and microbial ecology. The distribution of this capacity among microbial taxa, and the thermodynamic controls on EET in complex microbial communities, are not fully known. Microbial electrochemical cells (MXCs), in which electrodes serve as the electron acceptor or donor, provide a powerful approach to enrich for organisms capable of EET and to study their metabolism. We used MXCs coupled with genome-resolved metagenomics to investigate the capacity for EET in microorganisms present in a well-studied aquifer near Rifle, CO. Electroactive biofilms were established and maintained for almost four years on anodes poised mostly at -0.2 to -0.25 V vs. SHE, a range that mimics the redox potential of iron-oxide minerals, using acetate as the sole carbon source. Here we report the metagenomic characterization of anode-biofilm and planktonic microbial communities from samples collected at timepoints across the study period. From two biofilm and 26 planktonic samples we reconstructed draft-quality and near-complete genomes for 84 bacteria and 2 archaea that represent the majority of organisms present. A novel Geobacter sp. with at least 72 putative multiheme c-type cytochromes (MHCs) was the dominant electrode-attached organism. However, a diverse range of other electrode-associated organisms also harbored putative MHCs with at least 10 heme-binding motifs, as well as porin-cytochrome complexes and e-pili, including Actinobacteria, Ignavibacteria, Chloroflexi, Acidobacteria, Firmicutes, Beta- and Gammaproteobacteria. Our results identify a small subset of the thousands of organisms previously detected in the Rifle aquifer that may have the potential to mediate mineral redox transformations.